Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Pendidikan Islam - Syifa Nur Izzati Zahro; Siti Shopiyah (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2021)
The background of the authors doing research is that in 2019 the principal got second nomination as head of the school to perform grades. SD Islamic Plus As-Sa’adatain has many achievements in Islamic fields and excelled within Islamic education. So reaserchers want to know the principal’s leadership style and the headmaster’s efforts to improve Islamic education. The purpose of research is to know the headmaster’s leadership style in improving Islamic education at SD Islamic Plus As-Sa’adatain Cinere Depok. The method of research that the writer uses is qualitative research wtih a descriptive approach. This is because the writer described or presented a complete picture of the pricipal’s leadership style in improving Islamic education at SD Islamic Plus As-Sa’adatain Cinere Depok. Research shows that the leadership style used by the Islamic primary school principal plus ASAs-Sa’adatain is used as a favor to democratic leadership styles. The headmaster principal of SD Islam Plus As-Sa’adatain in solving problems and making decisions is always done with deliberation. The headmaster of principle leading (teachers, staff, students) is that the principal does not depend on formal, rigid power, being casual, firm, flexible, dicipline not too formal but is still responsible and able to mentor. The way headmaster Islamic elementary school plus As-Sa’adatain communicates with subbordinates (teachers, staff and students) of good, relaxed, courteous, polite, warm, harmonious, firm, depply communicative, and authoritative. The quality of Islamic education at Islamic SD Islam Plus As-Sa’adatain is already good, from its planning, its process, and its results